Interspecific resources: A major tool for quantitative trait locus cloning and speciation research (2010)
Positional cloning of the quantitative trait locus (QTL) still encounters numerous difficulties, which explains why thousands of QTL have been mapped, while only a few have been identified at the molecular level. Here, we focus on a specific mapping tool that exists in plant and animal model species: interspecific recombinant congenic strains (IRCSs) or interspecific nearly isogenic lines (NILs). Such panels exhibit a much higher sequence diversity than intraspecific sets, thus enhancing the contrasts between phenotypes. In animals, it allows statistical significance to be reached even when using a limited number of individuals. Therefore, we argue that interspecific resources may constitute a major genetic tool for positional cloning and for understanding some bases of speciation mechanisms. © 2010 Wiley Periodicals, Inc.